(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Prioritization of watersheds has grown in importance in natural resource management, particularly in the context of watershed management. The prioritizing approach finds the most important watersheds for management. Morphometric analysis has been widely used to prioritize watersheds since a basin’s watershed features indicate its physical and morphological traits, which are used to synthesize its hydrological response. The current work attempts to prioritize micro-watersheds in the Sindh Catchment of Ganderbal district, Jammu and Kashmir, using morphometric metricsand GIS methodologies. Various morphometric characteristics, namely linear and shape parameters, were obtained for each micro-watershed using Survey of India (SOI) top of sheets at 1:50,000 scale and assigned rankings based on value relationship to arrive at a computed value for a final ranking of the micro watersheds. The investigation found that the overall number and length of stream segments are greatest in first order streams and decrease as stream order increases.